2020
DOI: 10.5435/jaaosglobal-d-19-00179
|View full text |Cite
|
Sign up to set email alerts
|

Adding a Fibular Strut Allograft to Intramedullary Nail and Cancellous Autograft During Stage II of the Masquelet Technique for Segmental Femur Defects: A Technique Tip

Abstract: Reconstruction of segmental diaphyseal bone defects has been a major challenge in limb salvage surgery. Staged reconstruction as first described by Masquelet is a common strategy to deal with this problem in limb salvage surgery. One consequence of this technique is a time period of prolonged limited weightbearing while the segmental defect heals. The purpose of this study was to describe an adjunctive technique for stage II of the Masquelet procedure and retrospectively analyze the outcome and weight bearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
5
0
2
Order By: Relevance
“…First, a combination of cement spacer and induced membrane is used to fill the defected area. 22 Second, a biological implant replaces the cement spacer, which is impermeable, biological, and vascular-active. 22 However, autografts present some limitations such as morbidity in the donor site, pain, long hospitalization time, limited quantity, needing general anesthesia during the surgery, extended nonweight-bearing, graft hypertrophy, and the risk of hematoma and deep infection.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, a combination of cement spacer and induced membrane is used to fill the defected area. 22 Second, a biological implant replaces the cement spacer, which is impermeable, biological, and vascular-active. 22 However, autografts present some limitations such as morbidity in the donor site, pain, long hospitalization time, limited quantity, needing general anesthesia during the surgery, extended nonweight-bearing, graft hypertrophy, and the risk of hematoma and deep infection.…”
Section: Introductionmentioning
confidence: 99%
“…Distraction osteogenesis involves a modular-ring external fixator (Ilizarov apparatus) that stimulates the blood flow, allows early bearing, and creates good-quality bone tissue. , However, it is a technique that requires complex procedures leading to infections, nerve and blood vessel damage, chronic pain, and long hospitalization. , Masquelet and Begue developed a new concept based on a two-stage technique treating bone injuries in infected and noninfected conditions. First, a combination of cement spacer and induced membrane is used to fill the defected area . Second, a biological implant replaces the cement spacer, which is impermeable, biological, and vascular-active .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the use of structural allografts in IM reconstructions, there are only 2 reports in the literature. Niccolai et al 12 described this technique to treat a 6-cm segmental bone defect in an infected nonunion of the proximal femur, and Ramos et al reported the use of fibular strut allograft and cancellous autograft in 3 femoral bone defects 13 .…”
Section: Discussionmentioning
confidence: 99%
“…A different study compared the outcomes of fixation methods for treating bone defects with the IMT in the tibia and the femur 58 . A small study of only femoral defects suggested adding a fibular strut allograft after initial stabilization and placement of the cement spacer to improve patient outcomes 59 . All 3 of the patients achieved union and were able to bear weight as tolerated at an average of 3.6 months postoperatively.…”
Section: Sites For Use Of the Imtmentioning
confidence: 99%